ISLAMIC BRAND PERSONALITY: CRITICAL REVIEW IN PREVIOUS STUDIES FROM ISLAMIC PERSPECTIVE - Muhammad Izral Iberahim; Muhammad Saiful Islam Ismail; Muhamad Hasif Yahaya, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2025)
Brand personality is defined as the “set of human personality traits that are both applicable to and relevant for brands”. It is aimed at understanding the scientific contributions made by brand personality research and identifying its predominant traits as well as human characteristics. Islamic marketing scholars caught the attention by creating the characteristics of Islamic brand personality model which representing the Muslim consumers world widely in cosmetics, personal care, bakery, clothing Islamic and financial institutions. However, the proposition dimensions of Islamic brand personality seem to be familiar with conventional brand personality. Therefore, the objective of article is to explore by critically reviewed the previous model of brand personality and its dimensions. The present article employed qualitative study in form of library research. Finding indicated strength (i.e. Sharia indicator in Islamic brand personality, strengthening halal procedure in Islamic brand product, and assists the company in providing halal products and services. and weaknesses (i.e. (a) the dimensions of Islamic brand personality are based on conventional pivot, (b) immoral conduct on Islamic brand product, and (c) lack of awareness on the importance of halal brand in Malaysia) studies was reviewed. Present article proposed the component of Qawaid Fiqhiyah in explaining Islamic brand personality. This component able to assist firm to create personality of product in fulfilling demand of consumers align with Islamic conjunction.